Development of a High Performance 1280×1024 InGaAs SWIR FPA Detector at Room Temperature - Zhang, Jia-Xin; Wang, Wei; Li, Zai-Bo; Ye, Hai-Feng; Huang, Run-Yu; Hou, Ze-Peng; Zeng, Hui; Zhu, Hong-xia; Liu, Chen; Yang, Xue-Yan; Shi, Yan-Li (Frontiers in Physics, 2021)
A 1280 × 1,024 In0.53Ga0.47As short wave infrared (SWIR) focal plane array (FPA) detector with a planar-type back-illuminated process has been fabricated. With indium bump flip-chip bonding techniques, the InGaAs photodiode arrays were hybrid-integrated to the CMOS readout integrated circuit (ROIC) with correlated double sampling (CDS). The response spectrum is 0.9–1.7 μm. The test results show that the dark current density is 2.25 nA/cm2 at 25 °C, the detectivity D* is up to 1.1 × 1013 cm · Hz1/2/W, the noise electron is as low as 48 e− under correlated double sampling mode, the quantum efficiency is 88% at 1550 nm, and the operability is more than 99.9%. Moreover, the dark current and noise electron have been studied theoretically in depth. The results indicate that the diffusion current is the main contribution of the dark current, and the readout integrated circuit noise electron is the main source of FPA noise.